Measuring shari’ah governance practices: the development of shari’ah governance practices index (SGPi) for Islamic financial institutions in Malaysia - Nazmi, Nor Asila; Hassan, Rusni (Semarak Ilmu Publishing, 2024)
This paperfocuses on developing an index as a quantitative approach to assess Shari’ahgovernance in Islamic financial institutions (IFIs) in Malaysia. The objective is to construct and implement the Shari’ah Governance Practices Index (SGPi) to evaluate the extentof Shari’ah governance practices within the IFIs in Malaysia. The SGPi, formulated based on five principal dimensions –Board of Directors, Shari’ah Committee, Management, Shari’ahCompliant Functions, and Institution –is rooted in established standards pertinent to the period analysed. The methodological framework of the SGPi was employed on a dataset consisting of 31 Islamic financial institutions in Malaysia, encompassing Islamic banks, takaful operators, retakaful operators, and development financial institutions. This comprehensive approach facilitated a detailed evaluation of adherence to Shari’ah governance across various types of IFIs. The results indicate that, overall, Islamic financial institutions in Malaysia exhibit strong Shari’ahgovernance practices. However, a comparative analysis among different types of institutions revealed that Islamic banks tend to display slightly superior governance practices compared to takaful and retakaful operators, as well as development financial institutions. This study not only introduces a novel tool for measuring Shari’ahgovernance but also provides insights into the differing levels of compliance across various types of Malaysian IFIs, highlighting the significance of continuous improvement in governance practices to uphold the integrity and sustainability of the Islamic financial system.